Wide Variation in Opioid Prescribing Practices after Discharge in a Pediatric Teaching Hospital - Naiyi Sun; Benjamin Steinberg; Jacqueline Hanley; Lisa Isaac (Taylor & Francis Group, 2019)
Introduction/Aim: Opioid analgesics are frequently used for the treatment of acute pain in children following hospital discharge. In adults, opioid use can lead to overdose, diversion, and dependency. However, data on opioids prescription practices in the pediatric population is limited. The aim of this study is to characterize the amount and duration of opioids prescribed at time of discharge in children. Methods: We retrospectively identified all patients who were discharged from the hospital with an opioid prescription over an 18-month period in a pediatric teaching hospital. For each prescription, we recorded the type of opioid, dosing frequency, number of prescribed doses, and prescribing service. The patient's age, gender, weight, associated diagnosis, and hospital length of stay were also recorded. Results: During the 18-month period, we identified a total of 3784 patients who received 3871 discharge opioid prescriptions. The average age was 8.6 years (range: 0-18). Median oral morphine equivalent dose prescribed was 1.0 mg/kg/day (range: 0.043-11.146). Median duration of outpatient opioid therapy was 3.75 days (range: 0.17-50). The most common diagnoses were supracondylar fracture (n = 383, 9.9%), adeno/tonsillectomy (n = 299, 7.7%), femur fracture (n = 190, 4.4%), and posterior spinal fusion (n = 116, 3.0%). The median number (range) of days of opioid prescribed were: supracondylar fracture 5 (0.83-25), adeno/tonsillectomy 3.33 (0.83-10), femur fracture 5 (0.83-14), and posterior spinal fusion 6.67 (1.25-33.3). Discussion/Conclusions: We observed wide variations in dosage and duration of opioids prescribed at time of discharge. Further prescriber and patient education and guideline development are needed in the pediatric population.